2016
DOI: 10.1007/s10867-016-9423-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methotrexate on the viscoelastic properties of single cells probed by atomic force microscopy

Abstract: Methotrexate is a commonly used anti-cancer chemotherapy drug. Cellular mechanical properties are fundamental parameters that reflect the physiological state of a cell. However, so far the role of cellular mechanical properties in the actions of methotrexate is still unclear. In recent years, probing the behaviors of single cells with the use of atomic force microscopy (AFM) has contributed much to the field of cell biomechanics. In this work, with the use of AFM, the effects of methotrexate on the viscoelasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 57 publications
3
16
0
3
Order By: Relevance
“…The cellular relaxation time measured by AFM approach-reside-retract experiments is dependent on the loading force of the probe (Li et al, 2016b). Therefore, in order to make the results comparable, the experimental conditions of MCF-10A and MCF-7 cells are identical in the present study.…”
Section: Rusults and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The cellular relaxation time measured by AFM approach-reside-retract experiments is dependent on the loading force of the probe (Li et al, 2016b). Therefore, in order to make the results comparable, the experimental conditions of MCF-10A and MCF-7 cells are identical in the present study.…”
Section: Rusults and Discussionmentioning
confidence: 97%
“…The latter result can be attributed to the diverse viscoelastic behaviors of cytoplasm, whose flow enables the relaxation process of cells after indentation by the AFM tip (Moeendarbary et al, 2013); cytoplasm comprises heterogeneous components such as actin filaments, intermediate filaments, microtubules, nucleus, and organelles (Kirmizis and Logothetidis, 2010). Hence, a two-order Maxwell model can match the experimental stress relaxation curves well (Li et al, 2016a;Li et al, 2016b). Figure 2 shows the statistical contrast of elastic and viscoelastic properties between MCF-10A cells and MCF-7 cells measured by AFM approach-reside-retract experiments.…”
Section: Introductionmentioning
confidence: 97%
“…The results showed that Young's modulus alone failed to indicate the metastatic progression, but the combined biomechanical signatures of Young's modulus, adhesion, and calcium dynamics could effectively indicate the metastatic potential of prostate cancer cells, inspiring that performing studies on measuring multiple types of cell mechanics (e.g., Young's modulus, adhesion, relaxation time) and combining them with biological properties may help us to develop better biomarkers (or biomarker combination) for exactly indicating cell states and pathological changes. We have used AFM to simultaneously measure the elastic (Young's modulus) and viscoelastic properties (relaxation time) of cells [45], [59] by simultaneously recording force curves and stress relaxation curves during the AFM indentation process on cells via an oscilloscope linked to AFM, which facilitates us to acquire multiple mechanical parameters for characterizing cell behaviors. In order to examine the role of more types of cell mechanics besides Young's modulus, direct comparison studies on cancer cells and their normal counterparts, particularly on primary cells prepared from clinical cancer patients, are required.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…where F is the applied loading force of the AFM probe, A 0 is the instantaneous (purely elastic) response, A i are the [45], [59]. It should be noted that the elastic and viscoelastic properties of cells measured by AFM is dependent on the loading rate of AFM probe and the cell positions being probed also influence the measured Young's modulus of cells [60].…”
Section: B Cellular Viscoelastic Propertiesmentioning
confidence: 99%
“…(弹性系数、针尖形状)、基底、环境温度、探针加载 速度、细胞探测部位、培养基等 [6,29] . 利用AFM测量 细胞松弛时间受到加载力大小的影响 [27] . 因此, 为了 [14,15,30] .…”
Section: 数据分析unclassified